Perlindungan Tenaga Kesehatan Sukarela Di Daerah Konflik Bersenjata Menurut Hukum Internasional - Zian Rahmatullah; Josiana Agusthina Yvonne Wattimena; Arman Anwar (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: This study discusses the implementation of the protection of voluntary health workers in areas of armed conflict who work independently or under the auspices of national and international humanitarian organizations that have a very large role in providing medical assistance.Purposes of the Research: This study aims to examine and understand international law governing the protection of voluntary health workers in areas of armed conflict and to analyze the implementation of the protection of voluntary workers from the Syrian armed conflict. Methods of the Research: The research method used is normative juridical research or doctrinal legal research by examining legal literature using a law approach and a case approach. the use of legal material sources consists of primary, secondary, and tertiary legal materials. The technique of collecting legal materials is through literature study using qualitative analysis techniques.Results of the Research: The results showed that the protection for the safety of voluntary health workers, the security of buildings and medical equipment and their facilities in the war in Syria had not been carried out optimally in accordance with the provisions of international law, namely the 1949 Geneva Conventions and the 1977 Additional rotocol, because there were still acts of violation from the parties involved. conflict in Syria that threatens the safety of life, including the security of buildings and facilities for voluntary health workers.